A hierarchical Ti2Nb10O29 composite electrode for high-power lithium-ion batteries and capacitors. (May 2021) - Yuan, Tao; Luo, Sainan; Soule, Luke; Wang, Jeng-Han; Wang, Yachen; Sun, Dewang; Zhao, Bote; Li, Wenwu; Yang, Junhe; Zheng, Shiyou; Liu, Meilin
Graphical abstract: Abstract: Ti2 Nb10 O29 (TNO) is a suitable electrode for high-performance lithium-ion batteries and capacitors because of its large lithium storage capacity and high Li + diffusivity. Currently, the rate or power capability of TNO-based systems is limited by the poor electronic conductivity of the material. Here we report our findings in design, synthesis, and characterization of a hierarchical N-rich carbon conductive layer wrapped TNO structure (TNO@NC) using a novel polypyrrole-chemical vapor deposition (PPy-CVD) process. It was found that carbon coating with PPy–carbon partially reduces Ti and Nb cations, forms TiN, and creates oxygen vacancies in the TNO@NC structure that further increase overall electronic and ionic conductivity. Various defect models and density functional theory (DFT) calculations are used to show how oxygen vacancies influence the electronic structure and Li-ion diffusion energy of the TNO@NC composite. The optimized TNO@NC sample shows notable rate capability in half-cells with a reversible capacity of 300 mAh g −1 at 1 C rate and maintains 211 mAh g −1 at a rate of 100 C, which is superior to that of most M x Nb y O z materials. Full cell LiNi0.5 Mn1.5 O4 (LNMO)||TNO@NC lithium-ion batteries (LIB) and active carbon (AC)||TNO@NC hybrid lithium-ion capacitors (LIC) exhibited notable volumetric and gravimetric energy and power densities.